Multi Phase Center Processing of Ice Sounding Radar Signals for Across Track Surface Clutter Cancellation: Assessment of MVDR Beamformer, High Resolution DEM and DoA Methods for Improved Surface Clutter Cancellation - Scheiber, Rolf; Prats, Pau; Nannini, Matteo; Villano, Michelangelo; Walter Antony, John (2014)
ESA’s POLarimetric Airborne Radar Ice Sounder demonstrator (POLARIS) - build and operated by the Technical University of Denmark (DTU) - operates at P-band and features a multi-phase-center antenna for the purpose of surface clutter suppression. The first data suitable for the development and demonstration of suitable surface clutter cancellation methods were acquired in February 2011 during the IceGrav campaign in Antarctica. The purpose of the present study is to investigate and compare different methods for POLARIS surface clutter cancellation and to implement a Processing Tool to augment the along-track POLARIS processor developed by ESA, thus improving bedrock detectability. The present technical note concerns the activities of the CCN-1 with focus on implementing Direction- of- Arrival (DoA) methods to POLARIS data for surface clutter suppression and related performance analysis. A further focus is the investigation of the clutter suppression performance for different spaceborne scenarios. Further analyses concern investigations with improved DEM information and other characteristics of multi-aperture sounder data. The MVDR beamformer is introduced as an alternative to the optimum beamformer. The CCN activities documented in this technical note are divided into five major parts: The description of the MVDR beamformer and its comparison to the optimum beamformer are presented in section 2, together with the analytical comparison of two nulling techniques. The MVDR results with POLARIS data are discussed in section 4. In section 3 the clutter suppression performance is investigated when using high resolution digital elevation data, e.g. DEMs derived from TanDEM-X data (workpackage CCN-1B). The clutter suppression for POLARIS data using DoA methods is presented in section 5 (workpackage CCN-1A), the spaceborne scenario analysis is performed in section 6 (workpackage CCN-5), further investigations are reported in section 7: effects of clutter sidelobes (workpackage CCN-2), clutter estimation methods (CCN-4) ...